Longitudinal, Nationwide, Cohort Study to Assess Incidence, Outcomes, and Costs Associated With Complicated Urinary Tract Infection. (21st October 2019) - Carreno, Joseph J; Tam, Iris M; Meyers, Juliana L; Esterberg, Elizabeth; Candrilli, Sean D; Lodise, Thomas P
Abstract: Objective: Complicated urinary tract infections (cUTI) are common infections. Despite their frequency, limited data are available on the incidence and healthcare burden associated with cUTIs. This study details the epidemiology and 30-day health care resource utilization associated with cUTI in the United States. Method: This was a retrospective study of a PharmMetrics Plus database from January 1, 2013, to December 31, 2017. Inclusion criteria were as follows: age ≥18 years, International Classification of Diseases (Ninth or Tenth revision) cUTI diagnosis, and continuous enrollment for ≥6 months pre- and ≥30 days post index dates. Two mutually exclusive study cohorts for cUTI patients were identified based on the setting of the first observed cUTI diagnosis (inpatient [IP] and outpatient [OP]). Results: In total, 543 502 adults with cUTI met the inclusion criteria (104 866 IP cohort; 438 636 OP cohort). Mean (standard deviation) age was 48.1 (16.5) years and 68.1% were female. The overall incidence of cUTI was 1.01%, equating to approximately 2 882 195 annual cUTI cases in the United States. In the IP cohort, overall median (interquartile range [IQR]) 30-day health care costs were $13 028 ($4855–$26 781). Median (IQR) costs for the initial admission were $9441 ($2079–$19 027), with median (IQR) length of stay (LOS) of 4 (3–8) days. Among IP patients, 12 933 (12.3%) had a subsequent readmission. In the OP cohort, median (IQR) 30-day health care costs were $1531 ($305–$4998). Of OP patients, 40 457 (9.2%) had a 30-day admission. Conclusions: This study demonstrates that the economic burden associated with cUTIs is substantial, especially among patients requiring hospitalization. These findings highlight the need for new treatment approaches and antibiotics that avert hospitalization and reduce LOS. Abstract : This study suggests that there are over 2.8 million cases of cUTI per year in the United States, resulting in annual total costs in excess of $6 billion. The 30-day costs were largely due, in part, to the cost of inpatient care.